Finnish Farmers Feel They Have Succeeded in Adopting Cover Crops but Need Down-to-Earth Support from Research - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri; Känkänen, Hannu (MDPI AG, 2023)
In Finland, there is an ongoing adoption and learning process considering the cultivation of cover crops (CCs). The primary aim is to claim the benefits of CCs for agricultural production and ecosystems, which are both appreciated by Finnish farmers. A farmer survey with 1130 respondents was carried out to build an up-to-date understanding of how farmers have succeeded with CCs and whether they intend to continue with the use of CCs and to collect farmers’ views on knowledge gaps that should be filled by research or better knowledge sharing. The studied groups were farmers who had selected CCs as a registered measure in 2020 to receive agricultural payments. Data came from the Finnish Food Authority. Organic farmers were slightly more positive: they have had longer experience with CCs, but organic production is also more dependent on the ecosystem services provided by CCs. A high share of respondents agreed that their experiences with CCs have improved over time and were confident that CCs had become a permanent element of their production systems. Most of the farmers also agreed that the area under CCs would expand significantly in Finland and considered the cultivation of CCs as an effective measure to improve soil conditions. They often considered that challenges in adopting CCs were exaggerated and disagreed that bad experiences prevented them from expanding or continuing the use of CCs. The agricultural payment available for Finnish farmers to support the cultivation of CCs is quite reasonable (EUR 97 + EUR 50 per hectare) to compensate for any economic risks of CCs. Free word answers from the farmers highlighted research needs (in descending order) in the following areas: crop protection, sowing practices, the use of diverse CCs and their mixtures, and impacts on yield and profitability. Many of these are universal, i.e., have been reported elsewhere. Younger farmers (≤50 years) highlighted profitability, which is, in many European countries, a key barrier to the deployment of CCs. Farmers from the east and north regions, where the growing season is short, highlighted alternative CC choices as a knowledge gap.
Keywords: kyselytutkimus; maatalous; kasvinviljely; kestävyys; maanpeitekasvit; laji; adoption; cover crop; management; experience; farmer survey; knowledge gap